Ely Cathedral
The nave at Ely is, however, more typical of English Norman work than the simpler schemes of Gloucester and Hereford. Here the triforium has almost the same proportions as the lower arcade itself, and the roof. Each bay is defined by a single attached pilaster and shaft, which could have served as the springing for a stone vault. The The compound piers alternate in form, but obtains unity by the use of a common capital. Similar naves were built at Peterborough, Norwich and St. Albans, Before the eastern bay was absorbed into the octagon, just beyond the pointed arch of 1322, the nave consisted of thirteen bays. The regular coursing of masonry is remarkable.